IMPLEMENTASI PROGRAM PTSL DAN DAMPAK KEBIJAKAN AGRARIA TERHADAP KEPASTIAN HUKUM KEPEMILIKAN TANAH DI KABUPATEN BUOL - Baharudin, Alhamid; Morad, Ahmad M. (STISIPOL Mujahidin Buol, 2024)
The government has attempted to improve the agrarian legal system through various policies, including agrarian reform programs, land redistribution, and mass land certification. Agrarian reform, which was initiated with the aim of reducing inequality in land ownership, is often hampered by bureaucratic problems, corruption, and resistance from interested parties. Mass land certification implemented through the Complete Systematic Land Registration (PTSL) program is also expected to provide legal certainty for land owners. This research will be conducted at the Land Office in Buol Regency. The research method used is qualitative with a descriptive approach, so that it only presents the actual situation at the research location, data collection techniques using observation, interviews, and documentation. The results of the study show that the PTSL program has made a significant contribution to increasing legal certainty over land ownership in Buol Regency, the study shows that there are still various obstacles that hinder the effectiveness of this program. To achieve the program's objectives optimally, efforts are needed to improve various aspects, including increasing the capacity of human resources, infrastructure, coordination between institutions, and harmonization of regulations. Thus, it is hoped that the PTSL program can run better, improve community welfare, and support sustainable national development.